Assessment and management of shoulder pain at primary care level - Ntambue Kauta; Elma de Vries; Jean-Pierre du Plessis; Ben Grey; Cameron Anley; Basil Vrettos; Robert Dachs; Stephen Roche (South African Family Practice)
Most patients with shoulder pain will initially visit their community health centre, private general practitioner or family physician, with various levels of experience in the assessment and management of shoulder conditions. Shoulder conditions will range from early, simple ailments that can be treated in the primary care setting, to post-traumatic injuries and complex pathologies requiring the expertise of an orthopaedic surgeon or a fellowship-trained shoulder surgeon. Correct assessment of the patient’s shoulder condition at the index consultation is a prerequisite for appropriate management. This article sets out straightforward guidelines to help general practitioners confidently identify the patient’s source of shoulder pain and initiate an appropriate management plan at primary care level. Criteria for urgent and elective referral for specialist care are also outlined.